راءة تحليلية ف ان تشكيل مجالس محلية لإدارة شؤون المحافظات بالمشاركة مع هيئاتها التنفيذية يمثل امتداد حقيقي لمنهج الحكم الديمقراي النظام القانوني لتشكيل مجلس المحافظة والمجالس المحلية وفقا لقانون المحافظات غير المنتظمة في اقليم رقم (21) لسنة 2008 المعدل - راشد عبدالحمزة مصطفى; سالم كريم محمد; محسن جبر ابراهيم (Journal of College of Education, 2019)
The formation of local council to administered provincial affairs with participation executing bodies, , represent real extension of democratic governance approach to building Iraqi state under the constitution of 2005,but that not enough, what it couldn’t expect, where unless this council succees in performance its functions ,and service deliver to people of governorate and so resulting novelty experience of Iraq in the application decentralization and adoption elected council way at the level administrative of local governance, we find that appropriate action to assessment this experience and evolution practice by underlining areas of weakness of lending loon attention legislator and advocate to revision advocate including ensure their success and continue in framework objective assessment to this experiment, submitting this search called (analytic reading in the legal system to formation province’s council according to the law of governorate which are not part of region act no.21 of 2008 amended)which represent legal vision formation elected council at governance level(provincial council, district council municipal council),from where procedure formation and membership and the cases which that membership ends ,with find reflected aspects of meganism of constitute on their functions status ,and relationship with the other powers.